Dual Role of CO(2)/HCO(3)(−) Buffer in the Regulation of Intracellular pH of Three-dimensional Tumor Growths - Hulikova, Alzbeta (American Society for Biochemistry and Molecular Biology, 2011)
Intracellular pH (pH(i)), a major modulator of cell function, is regulated by acid/base transport across membranes. Excess intracellular H(+) ions (e.g. produced by respiration) are extruded by transporters such as Na(+)/H(+) exchange, or neutralized by HCO(3)(−) taken up by carriers such as Na(+)-HCO(3)(−) cotransport. Using fluorescence pH(i) imaging, we show that cancer-derived cell lines (colorectal HCT116 and HT29, breast MDA-MB-468, pancreatic MiaPaca2, and cervical HeLa) extrude acid by H(+) efflux and HCO(3)(−) influx, largely sensitive to dimethylamiloride and 4,4′-diisothiocyanatostilbene-2,2′-disulfonate (DIDS), respectively. The magnitude of HCO(3)(−) influx was comparable among the cell lines and may represent a constitutive element of tumor pH(i) regulation. In contrast, H(+) efflux varied considerably (MDA-MB-468 > HCT116 > HT29 > MiaPaca2 > HeLa). When HCO(3)(−) flux was pharmacologically inhibited, acid extrusion in multicellular HT29 and HCT116 spheroids (∼10,000 cells) was highly non-uniform and produced low pH(i) at the core. With depth, acid extrusion became relatively more DIDS-sensitive because the low extracellular pH at the spheroid core inhibits H(+) flux more than HCO(3)(−) flux. HCO(3)(−) flux inhibition also decelerated HCT116 spheroid growth. In the absence of CO(2)/HCO(3)(−), acid extrusion by H(+) flux in HCT116 and MDA-MB-468 spheroids became highly non-uniform and inadequate at the core. This is because H(+) transporters require extracellular mobile pH buffers, such as CO(2)/HCO(3)(−), to overcome low H(+) ion mobility and chaperone H(+) ions away from cells. CO(2)/HCO(3)(−) exerts a dual effect: as substrate for membrane-bound HCO(3)(−) transporters and as a mobile buffer for facilitating extracellular diffusion of H(+) ions extruded from cells. These processes can be augmented by carbonic anhydrase activity. We conclude that CO(2)/HCO(3)(−) is important for maintaining uniformly alkaline pH(i) in small, non-vascularized tumor growths and may be important for cancer disease progression.